The Persian version [videorecording (DVD)] - Keshavarz, Maryam; Noor, Niousha, 1982-; Mohammadi, Layla; Daneshmand, Bijan, 1958-; Ward, Bella; Byrne, Tom; Rostam, 1983-; Jäger, André; Amiri, Armin (Sony, 2023)
A Brooklyn woman must navigate her relationship with her cultural identity and her boisterous family. When the secrets of her life come to light during a family gathering in New York, she discovers parallels between her life and her mother's.